Exploring flow in the mobile interface context. (March 2020) - Johnson, Clark D.; Bauer, Brittney C.; Singh, Nitish
Abstract: While flow has been researched extensively in computer-mediated environments, it has been scarcely researched in the mobile interface context. Specifically, we have virtually no knowledge about what concrete traits of mobile interfaces (as opposed to user perceptions) encourage the flow state. Flow has been associated with many positive outcomes in human-computer interactions, making it vital for practitioners and scholars to understand the traits of mobile interfaces that encourage flow. Therefore, we synthesize the results of a literature search and a modified Delphi study to develop an inventory of traits and perceptions that can promote the flow experience. We provide initial evidence for the predictive validity of our inventory through a survey study which demonstrates that composite ratings of the inventory traits are positively associated with the flow state, which in turn, leads to compulsive usage and technostress. In doing so, this paper also extends flow research by exploring the potential negative outcomes of flow in the mobile interface context.